Home base and knowledge management in international ventures - Kuemmerle, Walter (Journal of Business Venturing, 2002)
This paper examines the scope and sequence of international activities carried out by nascent international ventures. Building on earlier research about foreign direct investment (FDI) and knowledge management in international firms and on the analysis of six international ventures the paper develops a number of propositions. We suggest that international ventures are conceived as ‘international’ because cross-border activities increase the chances of venture survival and growth. We also suggest that, in the early stages of international ventures, cross-border activities that augment the venture's knowledge base are more prevalent than cross-border activities that exploit the venture's knowledge base. Finally, the paper points out research trajectories for more detailed studies of knowledge management in international ventures.